Fingerprint Pattern Similarities Among Family Members: A Forensic Study of Hereditary Factors (Journal of Forensic Medicine & Toxicology, 2026)
Fingerprints are a vital tool for identifying criminals and disaster victims. While DNA testing is effective, it is expensive  and often a resource constraint for agencies like DVI. A more affordable solution is a fingerprint recognition system  integrated with population data. Interestingly, 46.4% of children share the same fingerprint pattern as their parents. This  similarity allows for the identification of underage victims or those without biometric data by matching their fingerprints  with living relatives. This research aims to analyze inherited fingerprint patterns within families. Fingerprint are obtained  from 36 subject of 2 big families comprising of a group of three levels of descent. The data obtained were analyzed by  elaborating the data in the form of tables and statistic test. There is a high prevalence of the Ulnar Loop fingerprint pat tern in Family A (75.33%) and Family B (78.57%). In Family A, Ulnar Loop was found on the middle finger of the right  hand (100%), and the middle finger of the left hand (93.33%). In Family B, grandparents with 100% Ulnar Loop patterns  passed this trait to all their children except for one with 90%. A significant relationship between family members and  fingerprint pattern similarity shows in both families (p value < 0.05). The Ulnar Loop showed a strong positive correlation (0.765***) in Family A and a strong negative correlation (-0.716**) in Family B, highlighting complex inheritance  patterns. These findings strongly indicate a significant familial influence on fingerprint patterns, particularly the Ulnar  Loop, affirming the potential for developing family-based fingerprint-matching technologies.
Keywords: forensic science; Forensic medicine; fingerprint pattern; family fingerprint; inheritance of fingerprint